Multicentre Clinical Simulation Evaluation of the ISO 80369-6 Neuraxial Non-Luer Connector. Issue 1 (March 2020) - Cook, T.M.; Wilkes, A.; Bickford Smith, P.; Dorn, L.; Stacey, M.; Kinsella, S.M.; Sharpe, P.; Phillips, P.
Abstract : ( Anaesthesia . 2019;74(5):619–629) The medical literature has reported incidents of "wrong route" administration of medicines, with much concern around errors involving neuraxial administration of intravenous agents. The risk of these errors increases when devices are fitted with the "universal" Luer connector. As a result, there have been efforts to introduce non-Luer neuraxial connectors into clinical practice. This article described a study conducted to assess the clinical usability and cross-connectability of non-Luer neuraxial connectors designed for anesthesia procedures. The study was conducted as part of the development phase of the International Organization for Standardization (ISO) 80369 standard, which included specifications for a series of 7 small-bore connectors of varying sizes designed to reduce the risk of accidental misconnections.